2004
DOI: 10.1016/j.placenta.2004.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Fetal growth restriction: a workshop report

Abstract: Intrauterine growth restriction (IUGR) is associated with significantly increased perinatal morbidity and mortality as well as cardiovascular disease and glucose intolerance in adult life. A number of disorders from genetic to metabolic, vascular, coagulative, autoimmune, as well as infectious, can influence fetal growth by damaging the placenta, leading to IUGR as a result of many possible fetal, placental and maternal disorders. Strict definitions of IUGR and of its severity are needed in order to eventually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
65
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 27 publications
0
65
1
3
Order By: Relevance
“…Numerous epidemiological studies focused on diverse populations from various parts of the world have substantiated these initial findings and expanded them to include increased susceptibility to a number of other pathophysiological conditions such as impaired glucose tolerance, type II DM, obesity, stroke, high blood pressure and non-insulin-dependent DM (7). By far, low birth weight (LBW) which occurs when a fetus fails to achieve its genetically determined growth potential (8), and subsequent hypertension has been the most studied. Although the mechanistic pathways underlying this association remain unclear, investigators using animal models to induce a sub-optimal fetal environment are providing critical support for the fetal programming hypothesis by demonstrating that exposure to adverse conditions in utero results in offspring with marked adaptive responses and adverse adult outcomes.…”
Section: Introduction To Fetal Programmingmentioning
confidence: 99%
“…Numerous epidemiological studies focused on diverse populations from various parts of the world have substantiated these initial findings and expanded them to include increased susceptibility to a number of other pathophysiological conditions such as impaired glucose tolerance, type II DM, obesity, stroke, high blood pressure and non-insulin-dependent DM (7). By far, low birth weight (LBW) which occurs when a fetus fails to achieve its genetically determined growth potential (8), and subsequent hypertension has been the most studied. Although the mechanistic pathways underlying this association remain unclear, investigators using animal models to induce a sub-optimal fetal environment are providing critical support for the fetal programming hypothesis by demonstrating that exposure to adverse conditions in utero results in offspring with marked adaptive responses and adverse adult outcomes.…”
Section: Introduction To Fetal Programmingmentioning
confidence: 99%
“…1,2 FGR is not a disease entity with a unique pathophysiology. 3 A variety of factors are involved, including congenital abnormalities, drug abuse, infectious diseases, and immunological and anatomical disorders. However, abnormal placentation (placental development) is observed in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors, including maternal, fetal and placental disorders, can influence fetal growth [13]. A diminished fetal growth is generally accompanied with a decrease of important substances for the body, such as glucose and Ca 2+ [14], amino acids [15] and fatty acids [16].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been demonstrated that IUGR is associated with Tables III and IV). a lower activity and expression of placental transport systems for essential amino acids, such as taurine, leucine and cationic amino acids [13]. Besides, it has also been shown that the reduced fetal weight that characterizes this condition is related to an incorrect adjustment of the placenta and poor development of the villi, conditions that lead to placental hypoxia [17] and consequently to low utero-placental perfusion and maternal-fetal transport of oxygen and nutrients [18].…”
Section: Discussionmentioning
confidence: 99%